Growth and Photoresponse of WS2/MoSe2 Lateral Heterostructure - Mingyuan Sheng; Xi Chang; Xiaojun Mao; Yang Gao; Xiaoyang Xuan; Haifen Xie; Haichuan Mu; Yueping Niu; Shangqing Gong; Min Qian (Advanced Electronic Materials, 2024)
Abstract The heterostructure of two‐dimensional transition metal dichalcogenide (TMDC) has garnered extensive attention, for the junction is the building block of a semiconductor device. However, the controllable synthesis of TMDC heterostructures of different transition metals and different chalcogen elements is still challenging because of the etching by atom substitution during the chemical vapor deposition (CVD) process. Here, a Mo─O transition state with lower energy is introduced to the edge of an as‐grown MoSe2 by using ultraviolet ozone treatment, to prevent the fast atom substitution of S for Se, and enable a stable growth of WS2/MoSe2 lateral heterostructure. A polymer‐free transfer method is developed based on capillary interaction, and atomic structure characterization confirms the high‐quality WS2/MoSe2 lateral heterostructure. The WS2/MoSe2 lateral heterostructure photodetector exhibits superior photoresponse compared to WS2 and MoSe2 devices, with a responsivity of 21.87 A W−1 and a detectivity of 4.2 × 1012 Jones at 350 nm. Kelvin probe force microscopy result reveals that the built‐in electric field within the heterojunction facilitates the effective separation of photogenerated electron‐hole pairs. This study carries profound implications for the CVD growth and polymer‐free transfer of TMDC heterostructures in photodetector applications.